The Role of E-WOM Communication in Changing the Image of Traditional Markets to Modern Markets - Eli Purwati; Widodo Muktiyo; Ahmad Puad Bin Mat Som; Krisna Megantari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the communication strategy of electronic word of mouth in the process of rebranding traditional markets into modern markets through TikTok social media. The case study was conducted in Songgolangit Market, Ponorogo, which underwent a visual transformation, services, and image with the support of digital promotion. The research uses a qualitative approach with data collection techniques in the form of participatory observation, in-depth interviews, and analysis of the content of the market’s official TikTok account. The results of the study show that electronic word of mouth communication built through visual content, visitor testimonials, collaborations with local influencers, and digital community-based campaigns has succeeded in increasing public perception, visitor interest, and positive image of the Songgolangit market. TikTok has proven to be an effective means of building an engaging rebranding narrative, while also accommodating the active engagement of the market community and visitors. The theoretical and practical implications of this research support the role of social media in the transformation of traditional markets in the digital age.